A multiple case study of homegrown franchising in Singapore from the franchisors' perspective - Kwek, Siew Hwee (2014)
The purpose of this project is to appraise the procedures involved in setting up homegrown franchises. Factors necessary to the success of a franchise are looked into. Problems encountered by the franchisors are also discussed and plausible reasons for their existence are dealt with. Specifically, the aim is to understand the entrepreneurial process and to analyse the problems, pros and cons and the elements of success of homegrown franchising.